The Relationship Between Household Food Sanitation Hygiene and Stunting Incidence in Toddlers - Noraida; Rahmawati; Uswatun Hasanah, Afifah (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2024)
In 2022, Barito Kuala district in South Kalimantan Province reported the highest number of stunting cases, particularly in Little Telan River Village, Tabunganen district. The area not only has a high prevalence of stunting but also a significant number of diarrhea cases. Sanitation, particularly concerning infectious diseases like diarrhea, is a key factor contributing to stunting among children. This is closely linked to household food hygiene and sanitation practices. This research aims to explore the connection between household food hygiene and the occurrence of stunting in young children in Telan River Village, Tabunganen district, Barito Kuala district. This study method is an analytical observational type supported by case control approach as design framework with a 1:1, with a total of 26 samples with data analysis using a chi-square test. The results of the hygiene study of household food sanitation (P − value = 0.018 < alpha = 0.05) have been linked to the occurrence of stunting in young children. There's no connection between the processing phase, hygiene and personal hygiene of the food miners and the stunting incident. There is a connection between food equipment and stunting events (P − value = 0.016 < alpha = 0.05). People are expected to get used to the application of proper food hygiene and sanitation in the handling of food in households. Pay attention to the validity and hygiene of the equipment used. Doing the right washing techniques.